Uncovering the significance of expanded CD8+ large granular lymphocytes in inclusion body myositis: Insights into T cell phenotype and functional alterations, and disease severity - McLeish, Emily; Sooda, Anuradha; Slater, Nataliya; Kachigunda, Barbara; Beer, Kelly; Paramalingam, Shereen; Lamont, Phillipa J.; Chopra, Abha; Mastaglia, Frank Louis; Needham, Merrilee; Coudert, Jerome David (Frontiers in Immunology, 2023)
Inclusion body myositis (IBM) is a progressive inflammatory myopathy characterised by skeletal muscle infiltration and myofibre invasion by CD8+ T lymphocytes. In some cases, IBM has been reported to be associated with a systemic lymphoproliferative disorder of CD8+ T cells exhibiting a highly differentiated effector phenotype known as T cell Large Granular Lymphocytic Leukemia (T-LGLL). We investigated the incidence of a CD8+ T-LGL lymphoproliferative disorder in 85 IBM patients and a group of 56 Healthy Controls (HC). Further, we analysed the phenotypical characteristics of the expanded T-LGLs and investigated whether their occurrence was associated with any particular HLA alleles or clinical characteristics. Blood cell analysis by flow cytometry revealed expansion of T-LGLs in 34 of the 85 (40%) IBM patients. The T cell immunophenotype of T-LGLHIGH patients was characterised by increased expression of surface molecules including CD57 and KLRG1, and to a lesser extent of CD94 and CD56 predominantly in CD8+ T cells, although we also observed modest changes in CD4+ and γδ T cells. Analysis of Ki67 in CD57+ KLRG1+ T cells revealed that only a small proportion of these cells was proliferating. Comparative analysis of CD8+ and CD4+ T cells isolated from matched blood and muscle samples donated by three patients indicated a consistent pattern of more pronounced alterations in muscles, although not significant due to small sample size. In the T-LGLHIGH patient group, we found increased frequencies of perforin-producing CD8+ and CD4+ T cells that were moderately correlated to combined CD57 and KLRG1 expression. Investigation of the HLA haplotypes of 75 IBM patients identified that carriage of the HLA-C*14:02:01 allele was significantly higher in T-LGLHIGH compared to T-LGLLOW individuals. Expansion of T-LGL was not significantly associated with seropositivity status for anti-cytosolic5'nucleotidase1A autoantibodies. Clinically, the age at disease onset and disease duration were similar in the T-LGLHIGH and T-LGLLOW patient groups. However, metadata analysis of functional alterations indicated that patients with expanded T-LGL more frequently relied on mobility aids than T-LGLLOW patients indicating greater disease severity. Altogether, these results suggest that T-LGL expansion occurring in IBM patients is correlated with exacerbated immune dysregulation and increased disease burden.